Analisis Penggunaan Ornamen Pada Desain Poster - Muhammad Fikri Haikal; Satriadi Satriadi (Universitas Negeri Makassar, 2023)
Posters are one of the visual communication media used to convey messages or information to the audience. This study aims to identify ornaments in poster design from the perspective of audience aesthetics by considering cultural developments in the Eastern hemisphere, namely China, the Middle East (Islam), and India. This study uses a literature review as a method to analyze poster designs focusing on ornamental needs in the design. The Interpretive Iconology (